The epidemiology of snake bite in Central Province and National Capital District, Papua New Guinea. - Lalloo, D; Trevett, A; Saweri, A; Naraqi, S; Theakston, R; Warrell, D (1995)
Snake bite is an important medical problem in some areas of Papua New Guinea and appears to be most common in the Central Province and National Capital District. The overall incidence for Central Province is 215.5 per 100,000 population, but Kairuku subprovince has an incidence of 526 per 100,000, which is amongst the highest in the world. The clinical pattern of envenoming also varies within the Province, suggesting that different species of snake may be responsible for bites in different areas. Most envenomed patients are bitten during daylight on the lower limb and are rarely able to describe the snake. The mortality rate in Central Province is 7.9 per 100,000; most patients die from ventilatory failure due to severe neurotoxicity. Mortality might be reduced by increased use of compression bandaging as a first aid measure, earlier treatment with antivenom and earlier referral to hospital.